Building a Competitive City through Innovation and Global Knowledge : The Case of Sino-Singapore Suzhou Industrial Park - Zeng, Doug Zhihua (World Bank, Washington, DC, 2016)
Special economic zones can be an effective instrument to promote industrialization if implemented properly in the right context. In China, starting in the 1980s, special economic zones were used as a testing ground for the country's transition from a planned to a market economy, and they are a prime example of China's pragmatic and experimental approach to reforms. One of the great special economic zone success stories in China is the Suzhou Industrial Park, a modern industrial township developed in the early 1990s through a Sino-Singapore partnership. It is successful not just in the economic sense, but also in terms of urban and social development in an eco-friendly way. One key lesson is that in a weak market environment, a facilitating and reform-oriented host government, coupled with foreign expertise and knowledge as well as a "whole value chain" approach can go a long way in developing urban-industry well-integrated special economic zones. This paper is intended to examine the success factors and key lessons of the Sino-Singapore Suzhou Industrial Park, which can be useful for other developing countries.